2022
DOI: 10.1038/s41598-022-23409-0
|View full text |Cite|
|
Sign up to set email alerts
|

Ocular biometrics and uncorrected visual acuity for detecting myopia in Chinese school students

Abstract: The study is to evaluate the performance of ocular biometric measures and uncorrected visual acuity (UCVA) for detecting myopia among Chinese students. Among 5- to 18-year-old Chinese students from two cities of China, trained eye-care professionals performed assessment of ocular biometrics (axial length (AL), corneal curvature radius (CR), anterior chamber depth) under noncycloplegic conditions using NIDEK Optical Biometer AL-Scan, distance visual acuity using retro-illuminated logMAR chart with tumbling-E op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The refractive data collected for this study were from noncycloplegic autorefraction, because there are difficulties of using cycloplegic in large population health screening, and it is challenging to implement in practice. However, it has been confirmed that there is a high agreement between cycloplegic refraction and noncycloplegic optometry results ( 51 ), the latter of which is adequate and has been recommended for screening in populations such as schools ( 52 , 53 ). Another limitation is the lack of detailed information about reading study time, outdoor activity time, time for extracurricular practical activities and time spent on online courses and digital devices among students in different type of schools before and during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The refractive data collected for this study were from noncycloplegic autorefraction, because there are difficulties of using cycloplegic in large population health screening, and it is challenging to implement in practice. However, it has been confirmed that there is a high agreement between cycloplegic refraction and noncycloplegic optometry results ( 51 ), the latter of which is adequate and has been recommended for screening in populations such as schools ( 52 , 53 ). Another limitation is the lack of detailed information about reading study time, outdoor activity time, time for extracurricular practical activities and time spent on online courses and digital devices among students in different type of schools before and during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of high myopia among children in China climbed year by year between 2014 to 2018 [34] , and children with low CC and long AL were much more likely to develop pathological retina changes and thus jeopardize their visual acuity if they were not effectively prevented and controlled [39] . The ocular biometric measures were not affected by accommodation, so it could be obtained from modern biometers objective and reliable results under noncycloplegic conditions [1] . The measurement process of AL was simple, easy to perform, and highly acceptable to patients.…”
Section: The Different Corneal Curvatures Of Childrenmentioning
confidence: 96%
“…Li et al [34] observed that the prevalence rate of high myopia defined by AL was higher than that defined by SE, which was evidence that lower CC could mask to some extent the decrease in SE and increase in AL. According to the study [1] , the prevalence rate of myopia in preschool children was low in China as well as in Europe, but increased with age as they entered the school years. Slowing the rate of myopia progression was a central goal of myopiarelated research, but preventing the onset of myopia was even more valuable [35] .…”
Section: The Different Corneal Curvatures Of Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Myopia is a common ocular health issue with an estimated global prevalence of 28.3%, especially affecting children and young adults in east and south-east Asian countries 1 , 2 . During the development of myopia, ocular biometrics are believed to play crucial roles 3 , 4 . Although the key mechanism of myopia mainly involves elongation of the eyeball and vitreous cavity 5 , changes of anterior segment structures are also suggested to play roles in myopia 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%